The Information Structure of Predicate Doubling - Muñoz Pérez, Carlos (2022)
In this paper we analyze the information structure of predicate doubling in Rioplatense Spanish (e.g., Leer, leyó ‘as for reading, she/he read’). We propose that in this construction the dislocated predicate functions as a contrastive topic in the sense of Büring (2003), that is, it evokes a set of alternative questions with which it contrasts. We argue that this characterization explains the “continuation effect” that predicate doubling exhibits, i.e., the fact that a predicate doubling sentence suggests a potential continuation that involves another predicate. Moreover, we show that this analysis correctly predicts the distribution of predicate doubling in embedding contexts.